The Responsibility of Heirs in Settling Replacement Money Claims for State Losses: A Comparative Study of Indonesia and Malaysia - Kontesa, Emelia; Zico Junius Fernando (Milthree Law Journal, 2025)
This article conducts a comparative analysis of the liability of heirs in Indonesia and Malaysia with respect to the settlement of replacement money (uang pengganti) arising from corruption cases. Both legal systems emphasize the principles of justice, individual rights protection, and the separation of responsibilities, thereby affirming that heirs are not personally liable for the corruptor’s actions. The liability of heirs is generally limited to the value of the estate actually inherited, and both jurisdictions recognize the right of heirs to renounce inheritance in order to avoid obligations linked to illicit assets. In Indonesia, the Anti-Corruption Law provides mechanisms for the confiscation of inherited property to recover state losses, although the legal framework remains general and lacks detailed regulation on the scope of heirs’ liability. Malaysia, under the Malaysian Anti-Corruption Commission Act 2009 and related statutes, similarly authorizes the seizure of inherited assets connected to corruption, while safeguarding heirs who neither control nor benefit from such assets. The findings highlight that, despite differences in regulatory clarity, both Indonesia and Malaysia adopt a balanced approach that allows the state to pursue restitution while protecting heirs’ rights through the option of inheritance rejection.